"You're Always in Transit, but the House Stays": Remitting, Restoring and Remaking Home in a Migrant Family House in Cuenca, Ecuador. Issue 5 (20th October 2022) - Boccagni, Paolo; Yapo, Stefania
ABSTRACT: Unravelling the emotional and relational bases of migrant transnational housing is an emerging challenge for research on home, family and migration. Based on a house biography in Cuenca, Ecuador, this paper reconstructs how a transnational family strived to preserve their past house by renovating it as a bed-and-breakfast. Building on narrative and ethnographic fieldwork, we explore how far a house with a commercial purpose and no permanent dwellers reproduces a sense of "home", and to the benefit of whom. We thereby connect this house biography to four societal questions: the retention of family memories, the interdependence between distant kin, the temporalities of housing and the commodification of the domestic. This fourfold analysis has fundamental implications for the meaning of home for migrants and for its interplay with housing, fixity and continuity, with an ultimate focus on what the house does, rather than on what it is.